192k views
4 votes
What is the answer to this equation ? : 6( 1R + 5 ) + 3R =

User Junken
by
5.8k points

1 Answer

5 votes
Use distributive property to remove the parenthesis. Distributive property allows us to "distribute" or share the one outside the parenthesis to all term inside the parenthesis.

6(1R + 5) + 3R
= 6 × 1R + 6 × 5 + 3R

Then work on the multiplication
= 6 × 1R + 6 × 5 + 3R
= 6R + 30 + 3R

Add the one with variable R together
= 6R + 30 + 3R
= 9R + 30
This is the simplest expression
User SnazzyBootMan
by
7.6k points